Corrigendum: CPT-TODIM method for interval-valued bipolar fuzzy multiple attribute group decision making and application to industrial control security service provider selection - Zhao, Mingwei; Wei, Guiwu; Guo, Yanfeng; Chen, Xudong (Technological and Economic Development of Economy, 2022)
Mengwei Zhao, Guiwu Wei, Yanfeng Guo, Xudong Chen, authors of the article "CPT-TODIM method for interval-valued bipolar fuzzy multiple attribute group decision making and application to industrial control security service provider selection", published in Technological and Economic Development of Economy, 27(5), 1186–1206, https://doi.org/10.3846/tede.2021.15044 inform that several errors occurred in page 1199, σ1 and σ3 values, comprehensive predominance matrix β, and page 1202, Table 8. This has now been corrected.The authors regret the errors.